Kewenangan Penerapan Aturan Terhadap Tindak Pidana Asusila Yang Korbannya Anak - Muhammad Rhazi; Iskandar A Gani; Dahlan Dahlan (Universitas Airlangga, 2022)
AbstractThis study aims to explain the handling of cases of immoral crimes whose victims are children in relation to the determination of the court to try and the authority of the investigation carried out by the National Police Investigators and the Aceh Wilayatul Hisbah Investigators associated with the concept of legal protection. The research method used is juridical empirical. Juridical research is using a statutory approach (dass sollen), while empirical research uses a field/interview approach (dass sein). The results of the study show that in Aceh Province in handling immoral crimes in which the perpetrators and victims are children, 2 (two) laws and regulations are applied, namely Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection and Aceh Qanun Number 6 of 2014 concerning Jinayat Law. Qanun jinayat is a positive law which in its application still requires higher legislation with the aim of being guided by the scope of the judiciary so that the ideal concept can be clearly seen in handling cases related to jinayat law. Meanwhile, the Qanun jinayat is a derivative of Law Number 11 of 2006 concerning the Government of Aceh.Keywords: Aceh; Immoral; Disparity. AbstrakPenelitian ini bertujuan untuk menjelaskan penanganan perkara tindak pidana asusila yang korbannya anak kaitannya dengan penentuan pengadilan yang mengadili dan wewenang penyidikan yang dilakukan oleh Penyidik Polri dan Penyidik Wilayatul Hisbah Aceh dikaitkan dengan konsep perlindungan hukum. Adapun metode penelitian yang digunakan bersifat yuridis empiris. Penelitian yuridis adalah menggunakan pendekatan peraturan perundang-undangan (dass sollen), sedangkan penelitian empiris menggunakan pendekatan lapangan/wawancara (dass sein). Hasil penelitian bahwa di Provinsi Aceh dalam penanganan tindak pidana asusila yang pelaku maupun korbannya anak diterapkan 2 (dua) aturan perundang-undangan yaitu Undang-undang Nomor 35 Tahun 2014 tentang Perubahan Atas Undang-undang Nomor 23 Tahun 2002 tentang Perlindungan Anak dan Qanun Aceh Nomor 6 Tahun 2014 tentang Hukum Jinayat. Qanun jinayat merupakan hukum positif yang dalam penerapannya masih memerlukan peraturan perundang-undangan yang lebih tinggi dengan tujuan untuk dipedomani oleh lingkup peradilan sehingga dapat dilihat secara jelas konsep ideal dalam penanganan perkara yang berkaitan dengan hukum jinayat. Sedangkan Qanun jinayat tersebut merupakan turunan dari Undang-undang Nomor 11 Tahun 2006 tentang Pemerintah Aceh.Kata Kunci: Aceh; Asusila; Disparitas.